Analysis of factors influencing cloud accounting adoption in Indonesian start-up companies using the technology acceptance model (TAM) and technology, organization, and environment (TOE) frameworks - Ardini Yaputri, Josephine; Widuri, Rindang (Edelweiss Applied Science and Technology, 2024)
This study was implemented to identify the connection between technology, environment, and organization factors and the impact on perceived benefits and its influence on adopting cloud accounting. This research developed the Technology, Organization, and Environment (TOE) framework, the Technology Acceptance Model (TAM), and the intention to adopt cloud accounting for start-up companies in Indonesia. Start-ups are pioneering businesses with flexible, independent natures and risk of failure. There were 340 valid responses collected from online questionnaires shared with start-up companies’ employees who were working in the accounting and finance departments. Those responses were processed with Smart PLS with SEM (Smart Equation Modelling). The result indicates that start-up companies are adopting cloud accounting based on their requirements and are not fully pushed by the TOE framework but are affected by perceived usefulness and ease of use. Start-ups will adopt cloud accounting, which is easy to use. However, to gain usefulness, the start-ups will be more pressured by their requirement instead of TOE as they tend to keep improving by their condition as independent and flexible companies.